CLASSROOM MANAGEMENT STRATEGY OF TEACHING ENGLISH PRONUNCIATION TO YOUNG LEARNERS AT INTENSIVE ENGLISH COURSE BANDA ACEH - Sariakin Sariakin (Jurnal Real Riset, 2021)
This research aims: (1) to find out how the teachers of Intensive English Course prepares classroom management strategy of teaching and learning process of pronunciation instruction, (2) to find out how the teachers of Intensive English Course conduct classroom management in teaching and learning process of pronunciation instruction, and (3) to find out how the teachers of Intensive English Course evaluates the result on classroom management in teaching and learning process of pronunciation instruction. This study belongs to qualitative research because only describes the situation and condition of applying pronunciation instruction at the course. Since the number of subjects of this researcher is only two teachers thus it should be taken as a sample and it is named data source. The instruments that are used to collect data are observation, interview, and documentation. The data gotten is analyzed by narration procedure and discussed. The result shows that in preparing classroom management strategy, the teachers prepare the program of year, syllabus, and program package. Next, in conducting classroom management strategy, the teachersapply student-centered approach. Besides, the teachers use three strategies in teaching and learning process namely: group discussion, role play, and drills. Next, in evaluating the result of teaching and learning process, the teachers evaluate students by using two kinds of tests namely on going process test and final test. The tests are written tests and conducted individually. Key Words: Classroom Management Strategy, Pronunciation, Teaching Learning Process